A three dimensional finite element analysis of insulated rail joints deterioration. (September 2018) - El-sayed, H.M.; Lotfy, M.; El-din Zohny, H.N.; Riad, H.S.
Abstract: Railroad corridors include a large number of insulated joints that act as elements of signalling and broken rail detection systems. Unfortunately, insulated joints are provided with a gap to safeguard electrical insulation causing stiffness discontinuity and stress singularity in rail sections in the proximity of insulated joints. Obviously, these problems will have a profound impact on diminishing the service life of insulated joints, and thus on advancing the maintenance costs. This research presents numerical simulations to investigate deterioration (both mechanical and electrical) of insulated joints. A parametric study was performed to quantify the effects of vertical wheel load, friction coefficient, joint inclination, and railhead edge filleting as well as the effect of joint width. The finite element modelling assessed that the joint inclination and arc fillet can effectively prolong the lifetime of joints through mitigations of stresses, strains, and reductions of insulating width. In addition, the friction level is severely affecting the mechanical deterioration at the rail surface in the proximity of rail joints. However, at sub–surface the influence of friction coefficient is relatively small. Finally, the effect of joint width was assessed to be trivial for the studied cases. Highlights: Railhead edges at insulated joints are roughly strained. Increased friction coefficient has a detrimental impact on the mechanical behaviour of insulated joints. Providing two fillet shaped arcs or an inclination to the insulated joint can attenuate the stress singularity. The action of joint width on the behaviour of insulated joints is tenuous.